2014
DOI: 10.37190/epe140408
|View full text |Cite
|
Sign up to set email alerts
|

Removal of methylene blue and methyl blue from wastewater by electrochemical degradation

Abstract: Electrochemical degradation of such dyes as methylene blue (BM-ylene) and methyl blue (BM-yl) was investigated using UV-Vis spectrophotometry, in order to be removed from the solutions, leading to discoloration of wastewater obtained under simulated laboratory conditions. The electrochemical degradation in the presence of 2 4 SO  ions, as well as in the presence of Clions were compared for the synthetic waters containing BM-ylene and BM-yl. The results showed that the fastest degradation and discoloration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…In the case of the standard, the phase angle maximum was shifted to lower frequencies and it has a comparative value, around −28.7°, with that of Cu/SE/HCl sample. The impedance response (log|Z|) has the highest value of around 2.38 (meaning 240 Ω cm −2 ) for Cu/PVAC/HCl sample implying the highest polarization resistance (charge transfer resistance) compared to uncoated samples. Consequently, the polymer coating reaches a good protection performance for copper corroded in 10 −2 mol L −1 HCl solution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of the standard, the phase angle maximum was shifted to lower frequencies and it has a comparative value, around −28.7°, with that of Cu/SE/HCl sample. The impedance response (log|Z|) has the highest value of around 2.38 (meaning 240 Ω cm −2 ) for Cu/PVAC/HCl sample implying the highest polarization resistance (charge transfer resistance) compared to uncoated samples. Consequently, the polymer coating reaches a good protection performance for copper corroded in 10 −2 mol L −1 HCl solution.…”
Section: Resultsmentioning
confidence: 99%
“…The organic thin films obtained by the electropolymerization of specific monomers can be electrodeposited on metal surfaces using cyclic voltammetry (CV) or potentiodynamic measurements conducted in electrolyte solutions containing the respective monomers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous our studies we reported the results of our research on the electrochemical stability of some drugs, and of some dyes, as follows: metronidazole, benzocaine, hematoxylin, Brilliant Blue, Methylene blue, Methyl blue, Methylorange .…”
Section: Introductionmentioning
confidence: 99%
“…Similar results have been reported previously by several authors while determining the most suitable kinetic model for 1-phenylazo-2-naphthol (PAN), alizarin saphirol (AS), indigo carmine (IC) [1,[27][28][29][30]. On the other hand, other researchers determined the pseudo-first order as a suitable model to describe the kinetics for the following dyes: Rhodamine B (RhB), alizarin red S (ARS), methyl orange (MO), congo red (CR), methylene blue (BMylene), methyl blue (BM-yl) [14,20,27,29,[31][32][33][34].…”
Section: Determination Of Kinetic Model For Mb Removalmentioning
confidence: 99%